Perilaku Moral Remaja dalam Perspektif Budaya - Rizal, Yenni (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2017)
This study aims to describe adolescent morality behavior within culture perspective. The used instrument to identify adolescent morality behavior is morality behavior scale which the aspects are researched such as cognitive, affective, and psychomotor. The participant in this research are adolescent in age 15 to 18 at Sekolah Menengah Kejuruan Negeri 8 Pontianak, West Kalimantan. The researcher applied quantitative research during the research procedure. The analysis data is implemented that utilize SPSS program; the result shows that respondent indicated adolescent morality behavior tendency based on gender. Adolescent morality behavior, based on result of research, categorizedfemale in reaching higher score than male for three aspects are cognitive, affective, and psychomotor which cognitive as the highest one. To conclude this research, is the gender as one of culture construct that explained either female or male adolescent has difference in morality behavior.